KAPASITAS ADSORPSI SERBUK NATA DE COCO (BACTERIAL SELLULOSE) TERHADAP ION Pb2+ MENGGUNAKAN METODE BATCH - Saputri, C. A. (Jurnal Kimia (Journal of Chemistry); Vol.14 No.1 Januari 2020, 2020)
The purpose of this research is determine adsorption capacity of nata de coco powder to the ion Pb 2+ . Nata de coco is a cellulose derived from the fermentation of Acetobacter xylinum bacteria. Nata de coco powder is made by  mashed nata de coco then heated at 80 o C,  mashed and sifted up to 30-40 mesh size. Characterization includes  determination of  moisture content, ash content, density and amount of iodine adsorbed. Optimum contact time using batch method with time variation are 20, 40, and 60 minutes. The determination of the capacity of adsorption using the isotherm pattern of Langmuir and Freundlich using variation  concentrations Pb 2+ 15, 30, 45, and 60 ppm. Amount of adsorbed ion Pb 2+ measured by using the Atomic Absorption Spectrophotometry (AAS) at a maximum wavelength of  Pb 2+ that is 283 nm. The results showed that the optimum time was reached at 60 minutes. Adsorption pattern  approach to the Freundlich’s Isotherm models with an adsorption capacity  2.34 mg/g.   Keywords: adsorption capacity, Freundlich’s isotherm, ion Pb 2+ , nata de coco powder